Electronic structure and Thermoelectric Properties of Hybrid Organic-Inorganic Perovskites [NH3-(CH2)3-COOH]2CdCl4 - Ouaaka, El Mustafa; Kassou, Said; Ettakni, Mahmoud; Sayouri, Salaheddine; Khmou, Ahmed; Khechoubi, El Mostafa (Physics and Chemistry of Solid State, 2021)
In this work, we conducted the first principle calculation of electronic structure and transport properties of [NH3-(CH2)3-COOH]2CdCl4 (Acid-Cd). The generalized gradient approximation is used in structural optimization and electronic structure. The theoretical band gap value found is in good agreement with experimental. Electronic thermal conductivity, electrical conductivity, Seebeck coefficient (S) and figure of merit (ZT) have been calculated using semi-local Boltzmann theory to predict the thermoelectric characteristic of the studied materials.